Redescription of four species of Spio and Microspio (Polychaeta, Spionidae) from the Kuril Islands and Peter the Great Bay, northwest Pacific - Bick, Andreas; Meißner, Karin (Zootaxa, 2011)
The type material and additional specimens deposited in the collections of the Zoological Institute of the Russian Academy of Sciences, Saint Petersburg, of four poorly known species of Microspio and Spio, M. kussakini Chlebovitsch, 1959, S. kurilensis Buzhinskaya, 1990 comb. nov., S. picta Zachs, 1933 and S. unidentata Chlebovitsch, 1959, were examined. All species occur in intertidal or shallow subtidal areas of the northwest Pacific Ocean. Previously available taxonomic information on these species was from brief original descriptions and very few additional publications. A redescription of these four species is presented including detailed descriptions and illustrations of morphological characters. Comments on the taxonomic status are added. Diagnostic characters of Microspio and Spio species are discussed.